IMPACT OF HUMAN CAPITAL FLIGHT ON ECONOMIC DEVELOPMENT OF ABIA STATE UNIVERSITY, UTURU - Sunday Umeh, Chijioke; Nonye Ogbonna, Peace; Chinonso Agu, Patrick (African Journal of Social and Behavioural Sciences, 2026)
This paper examined the impact of human capital flight on the institutional development of Abia State University, Uturu. The objective is to find out the causes of human capital flight, its effects, and the various strategies to reduce it, as well as improve the institutional development of the University. A survey research design was adopted for the study, utilizing a mixed-method approach that combined both primary and secondary data collection. The study is anchored in structural functional theory. The research instrument was tagged “Human Capital Flight and Institutional Development Survey Questionnaire” (HCFIDSQ), and a reliability coefficient of 0.80 was obtained. Data collected were analyzed using frequency counts, percentages and mean. The hypotheses were tested using Pearson’s Product-Moment Correlation Coefficient at a 0.05 significance level. The findings showed that there was a relationship between the causes of human capital flight, its effects and the dwindling development in the University, and that the institution management expressed interest in using the various strategies which could help them to reduce the rate of brain drain, but could not effectively utilize them. Based on the findings, it was recommended that the government should regularly organize workshops/seminars to educate the university management on the need to effectively utilize the various strategies to reduce brain drain, and create an effective and efficient institutional policy capable of establishing a platform for entrepreneurship, as well as create opportunities to enhance development in the Abia State University.